Seed Industry Analysis in Asia: Toward better metrics and policymaking - Spielman, David J.; Kennedy, Adam (International Food Policy Research Institute, 2014)
Our ability to select desirable biological characteristics of plants through applications of modern science creates remarkable abundance in agriculture and is also the uncomplicated reason why many governments in industrialized and developing countries have historically invested in improving cultivated crop varieties (“cultivars”) through applications of modern science. When combined with other modern inputs and good crop management practices, improved cultivars can enhance crop yields significantly and subsequently drive agricultural productivity growth (Evenson and Gollin 2003; Rosegrant and Hazell 2000; Rosegrant and Evenson 1992).